Effects of a group mindfulness-based cognitive programme on smartphone addictive symptoms and resilience among adolescents: study protocol of a cluster-randomized controlled trial - Anson Chui Yan Tang; Regina Lai Tong Lee (BMC, 2021)
Abstract Background Smartphone addiction in adolescent is a significant global health issue since the last decade. Evidence has shown that the uncontrolled use of smartphone would lead to undesirable impact on their growth and development. However, evidence-based interventions to manage adolescents' smartphone addictive behaviors is lacking. The proposed study aims to examine the effect of a group mindfulness-based cognitive programme(MBCP) on resilience, smartphone behavior and addictive symptoms in young adolescents. Methods It is an open-label, parallel-group, cluster-randomized controlled trial with repeated measurement analysis. Four primary schools in Hong Kong will be recruited and randomly allocated in a ratio of 1:1 to the intervention/control group. A convenience sample of 240 class level 5 primary school students, 60 from each school, will be recruited. Participants in the intervention group will receive a 12-week MBCP which comprises 90-minute supervised practice at school and daily home practice. Resilience will be measured by Connor-Davidson Resilience Scale - 25 (Chinese version); smartphone behavior will be represented by time spent/day using the smartphone and types of functions used; addictive symptoms will be measured by Smartphone Addiction Scale-Short Version (Chinese Version). Baseline assessment(T0) will be conducted before the intervention starts. Post-tests will be conducted in weeks 4, 8, 12 of the intervention, and 3 months follow-up. Intention-to-Treat analysis will be applied to the variables. Generalized Estimating Equation model will be used to compare differences in resilience scores, smartphone behavior and addiction scores between and within groups, adjusted for socio-demographic factors. P < 0.05 with two-tailed test will be regarded as significance. Discussion It is expected that adolescents will demonstrate better resilience and lesser smartphone addictive symptoms after joining the MBCP. The study will be the first provided empirical evidence to support the promising application of MBCP to manage smartphone use among adolescents. It introduces community stakeholders including community nurses a non-invasive and simple-to-administer intervention to tackle problematic smartphone use among adolescent clients. Trial registration Chinese Clinical Trial Registry, ChiCTR2000033273, Registered on 26 May 2020.